2011
DOI: 10.1016/j.scient.2011.11.028
|View full text |Cite
|
Sign up to set email alerts
|

High resolution imaging of IgG and IgM molecules by scanning tunneling microscopy in air condition

Abstract: A scanning tunneling microscope is a powerful tool for obtaining micrographs from conductive and semiconductive materials. The imaging technique has recently been improved for microscopy of nanostructured biomaterials on highly ordered atomic surfaces. We describe, here, high resolution imaging of individual IgM and IgG using a scanning tunneling microscope (Nama-STM) in air condition. The biomolecules were immobilized on the surface of Highly Ordered Pyrolytic Graphite (HOPG). Obtained micrographs could revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…During the scan, the current set point was decreased from 0.1 nA to 50 pA. Rough data were processed by using median (middle range) and low pass Gaussian (high range) filters [13].…”
Section: Scanning Tunneling Microscopy (Stm) Analysismentioning
confidence: 99%
“…During the scan, the current set point was decreased from 0.1 nA to 50 pA. Rough data were processed by using median (middle range) and low pass Gaussian (high range) filters [13].…”
Section: Scanning Tunneling Microscopy (Stm) Analysismentioning
confidence: 99%
“…Rough data were first processed using line adjust, plain adjust and average filters of the NAMA-STM Nanoanalyzer software. Then, the colouring process was tested on the obtained micrographs for different levels [19].…”
Section: Characterization Of Dna Nanotubes By Stmmentioning
confidence: 99%
“…It has previously been observed that in the obese state a higher fraction of IMCL is present as peroxidized lipids (4-hydroxynonenal (4-HNE)) [36], a lipid-derived reactive aldehyde with proven insulin-desensitizing properties [37]. Indeed, increased 4-HNE protein adducts have been observed in skeletal muscle of insulin resistant humans [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, LD expansion may originate from coating of the LD with PLIN5 and its inhibitory effect on myocellular LD lipolysis, either by binding to the major triglyceride lipase ATGL [37] or by binding to the co-activator of ATGL, being CGI-58 [38]. In trained athletes, high levels of IMCL and high insulin sensitivity go along with high levels of PLIN5 [16,17], indicating that PLIN5 may modulate insulin sensitivity under conditions of high lipid load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation